Membentuk Karakter Kewirausahaan Peserta Didik Melalui Koperasi Siswa Pada SMK Negeri 1 Jabon - Moch. Dicky Riza (Jurnal of Management and Social Sciences, 2025)
The development of the Indonesian nation at this time is development in the economic field to improve the standard of living and welfare of the entire nation. So how can we direct students toward an active financial life? This can be achieved by teaching entrepreneurial activities to students, so that students develop entrepreneurship, for example through school cooperatives. Business values ​​(characteristics) are conveyed through actual sales activities in school cooperatives. Where some students are directly involved in the management of the student's school cooperative itself. Based on this background, the objectives of this research are: (1) Describe student cooperative activities at SMK Negeri 1 Jabon Sidoarjo to form student entrepreneurship participants. (2) description of student entrepreneurship through student cooperatives at SMK Negeri 1 Jabon Sidoarjo. (3) Describe the factors that support and hinder the growth of entrepreneurial creativity in students of SMK Negeri 1 Jabon Sidoarjo through student cooperatives. The research method used to write this research is descriptive qualitative research taken from various journal articles and the author collects and analyzes various references to these articles. All data that is summarized in scientific articles on qualitative data does not use numbers, tables, g-tables or graphs, but rather in the form of descriptions from various sources or scientific journal references. Research using descriptive techniques is data analysis by describing or illustrating the collected data just like that, without drawing conclusions. The following can be interpreted from data analysis: 1) Activities that aim to form the entrepreneurial spirit of students are as direct learning and student participation in various activities in cooperatives, and entrepreneurial activities of students are formed following the activities of various cooperatives. Entrepreneurial values ​​among students are leadership, confident, communicative, responsible, honest handling, diligent, cooperative and willing to take risks. (2) Entrepreneurial skills developed by students, for example the ability to provide good service and communication, manage and make good use of time, lead cooperatives well and think smartly to seize opportunities. (3) The enabling aspect is encouragement or motivation from parents of students and students who have the desire to become entrepreneurs, while two things that become inhibiting factors are: Lack of funds and geographic location